PENGARUH PENGGUNAAN CHAT GPT DALAM PEMBELAJARAN TERJEMAH INDONESIA-ARAB - Nurfaiza (STAI Nurul Huda Kapongan Situbondo, 2024)
This study aims to examine the impact of ChatGPT use in the process of Indonesian-Arabic translation learning at Pondok Pesantren Nurul Huda Kapongan, Situbondo. The research investigates how ChatGPT influences the efficiency, speed, and accuracy of translation while highlighting the challenges faced by students, such as cultural context errors, inaccuracies in complex sentence structures, and over-reliance on technology. This research also explores the role of ChatGPT in supporting independent learning outside formal classes. A qualitative approach was employed, using interviews, participant observation, and documentation analysis to collect data. The findings revealed that ChatGPT significantly improved translation speed and accuracy for most students, with 90% accuracy on average. However, issues such as literal translation and cultural context inaccuracies persisted. Additionally, over-reliance on ChatGPT led to a reduced depth of understanding of the Arabic language, indicating that while AI can enhance learning efficiency, it must be accompanied by human guidance to address its limitations. The study concludes that ChatGPT is a valuable tool for enhancing translation learning but should be integrated into the curriculum with careful monitoring to ensure students deepen their cultural and contextual understanding of the Arabic language. The study provides insights into how AI can be used to support learning in Islamic education, especially in remote areas with limited resources.